Kesuksesan Komisi Pemilihan Umum dalam Menyelenggarakan Pemilu 2019 - Paul Adryani Moento (Politicon : Jurnal Ilmu Politik, 2020)
The system that Indonesia is currently using as a form of realizing people's sovereignty is to hold elections. Both elect legislators and presidents who in principle are to make the community prosperous and prosperous by maximizing the available potential by managing natural resources in accordance with the mandate of the 1945 Constitution Article 33 Paragraph 1 to Paragraph 4. The purpose of this paper is to find out the benefits from elections for the welfare of the people. This assessment method uses a qualitative approach by tracing matters of public benefit to the electoral system and using data search techniques in the form of literature reviews or literature studies and using triangulation techniques to validate the data the authors get from library research. The results of the study show that elections are useful as a tool for democracy, a means of community participation, solutions to change leadership, legitimizing elected leaders, where people submit their aspirations, socialize and establish relationships.